2016
DOI: 10.4103/2321-1407.183156
|View full text |Cite
|
Sign up to set email alerts
|

Correction of transverse maxillary deficiency and anterior open bite in an adult Class III skeletal patient

Abstract: Transverse maxillary deficiency may be associated with sagittal or vertical problems of the maxilla or mandible. It may contribute to unilateral or bilateral posterior crossbite, anterior dental crowding, and unesthetic black buccal corridors on smiling. An adequate transverse dimension is important for stable and proper functional occlusion. Surgically, assisted rapid palatal expansion has been the treatment of choice to resolve posterior crossbite in skeletally mature patients. The following case report pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Surgically, assisted rapid palatal expansion has been the treatment of choice to resolve posterior crossbite in skeletally mature patients. 15 The correct diagnosis of the severity of transverse deficiency is essential to achieve adequate treatment. In order to make the best therapeutic decision on the different cases of maxillary hypoplasia in patients with advanced skeletal maturation, the different factors must be comprehensively assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgically, assisted rapid palatal expansion has been the treatment of choice to resolve posterior crossbite in skeletally mature patients. 15 The correct diagnosis of the severity of transverse deficiency is essential to achieve adequate treatment. In order to make the best therapeutic decision on the different cases of maxillary hypoplasia in patients with advanced skeletal maturation, the different factors must be comprehensively assessed.…”
Section: Discussionmentioning
confidence: 99%
“…It is a combination of orthodontic and surgical procedures that causes considerable expansion of the maxillary apical base and palatal vault, providing a dental arch space, this technique may include bilateral osteotomy of the zygomatic pillars and palatal suture with or without separation of the pterygoid processes. 15 Lee et al suggested a non-surgical approach to RME as an alternative to optimize the potential of skeletal expansion in patients with advanced skeletal maturation using mini-implants (miniscrewassisted rapid palatal expansion, MARPE), this MARPE applies forces to the miniscrews placed close to the midpalatal suture, differently from other techniques, which apply forces to the teeth or periodontium, therefore avoiding the need of osteotomies. [16][17][18] MARPE is a less invasive option than SARME, has a skeletal effect, fewer dentoalveolar effects, no surgical risks and reasonably stable results, in addition to being more affordable financially.…”
Section: Absolute Transverse Discrepancymentioning
confidence: 99%